2006
DOI: 10.1111/j.1365-2389.2006.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Lignin turnover in an agricultural field: from plant residues to soil‐protected fractions

Abstract: Lignin has long been suspected to be a major source of stable carbon in soils, notably because of the recalcitrant nature of its polyphenolic structure relative to other families of plant molecules. However, lignin turnover studies have produced conflicting results, most of them suggesting that large proportions of plant-residue lignin decompose within a year of incorporation into soils. Here, we propose a tworeservoir model where lignin in undecomposed plant residue (Lp) can either reach soil fractions where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
51
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 30 publications
(63 reference statements)
8
51
2
1
Order By: Relevance
“…4). These two seemingly contrasting observations can be reconciled if two lignin pools are assumed with similar parameters as determined by Rasse et al (2006) at Les Closeaux. The existence of a large pool (approx.…”
Section: Specific Compoundsmentioning
confidence: 95%
See 3 more Smart Citations
“…4). These two seemingly contrasting observations can be reconciled if two lignin pools are assumed with similar parameters as determined by Rasse et al (2006) at Les Closeaux. The existence of a large pool (approx.…”
Section: Specific Compoundsmentioning
confidence: 95%
“…A recent study by Rasse et al (2006) found that observed changes in lignin isotope ratio can be explained by a twocompartment model. The model assumes an unprotected lignin pool and a stabilized pool.…”
Section: Specific Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apparently there was a minor contribution of fresh plant material to this SOM (Nierop et al, 2005). And indeed, it has also been reported for similar soil types that lignin rapidly decomposes and does not contribute as much to SOM as other, potentially more labile compounds may (Dignac et al, 2005;Rasse et al, 2006;Heim and Schmidt, 2007). The differences in natural 13 C abundances allowed for the calculation of turnover times for the pyrolysis products.…”
Section: Pyrolysis Productsmentioning
confidence: 99%